Iatrogenic femoral nerve palsy after a routine knee ligament surgery - Prithvi Raj, Prunav Adhav; Mohan, Madan; Pilar, Anoop; Kodi, Harish; S. Amaravathi, Rajkumar (International Journal of Research in Orthopaedics, 2023)
Peripheral nerve injuries following surgery can have a significant impact on the rehabilitation process. We report a case of a 25-year-old male who was unable to actively raise his leg and extend his knee following knee surgery (Arthroscopic Posterior cruciate ligament reconstruction and Posterolateral corner reconstruction). Following the surgery, it was noticed that the patient’s knee range of movements and power was 0/5 as per the Medical Research Council (MRC) scale. On subsequent evaluation, it was found to be due to femoral nerve axonal neuropathy. We report such a case of femoral nerve axonal neuropathy following arthroscopic posterior cruciate ligament (PCL) reconstruction and posterolateral corner (PLC) reconstruction.